2018
DOI: 10.1038/s41598-017-18418-3
|View full text |Cite
|
Sign up to set email alerts
|

Past visual experiences weigh in on body size estimation

Abstract: Body size is a salient marker of physical health, with extremes implicated in various mental and physical health issues. It is therefore important to understand the mechanisms of perception of body size of self and others. We report a novel technique we term the bodyline, based on the numberline technique in numerosity studies. One hundred and three young women judged the size of sequentially presented female body images by positioning a marker on a line, delineated with images of extreme sizes. Participants p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
74
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(80 citation statements)
references
References 33 publications
5
74
1
Order By: Relevance
“…Our findings add to previous studies suggesting that assimilative serial dependence occurs for higher level judgments such as face and body attractiveness (Alexi et al, 2018;Taubert, Van der Burg, et al, 2016;Xia et al, 2016), and extends the scope of assimilative serial dependences further into the domain of aesthetic judgments of artwork. It remains unanswered, however, at which stage of aesthetic judgment this positive bias occurs.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Our findings add to previous studies suggesting that assimilative serial dependence occurs for higher level judgments such as face and body attractiveness (Alexi et al, 2018;Taubert, Van der Burg, et al, 2016;Xia et al, 2016), and extends the scope of assimilative serial dependences further into the domain of aesthetic judgments of artwork. It remains unanswered, however, at which stage of aesthetic judgment this positive bias occurs.…”
Section: Discussionsupporting
confidence: 82%
“…With one degree of freedom given to the magnitude of prediction (a scale factor K which weights the entire right-hand side of Equation 3), the scaled model gives an improved fit of R 2 ¼ 0.8 when K has a value of 0.67 (blue continuous line in Figure 3A). In line with previous serial dependence studies showing assimilative patterns (Alexi et al, 2018;Bliss, Sun, & D'Esposito, 2017;Fischer & Whitney, 2014;Fritsche et al, 2017), our finding suggests that aesthetic ratings are systematically biased towards information from the recent past.…”
Section: Serial Dependence In Aesthetic Judgmentssupporting
confidence: 91%
See 2 more Smart Citations
“…Two recent papers [ 2 , 3 ] introduced a new psychophysical paradigm, serial dependence , which provided direct evidence of how a system incorporates past information into the perception of the current stimulus. These effects have now been confirmed with a variety of stimuli and tasks, from simple orientation judgements [ 3 5 ], numerosity [ 2 ], position [ 6 , 7 ], facial identity and expression [ 8 , 9 ], eye gaze [ 10 ], pulchritude [ 11 ] or body size [ 12 ], to complex judgements such as summary statistics [ 13 ], variance [ 14 ] and confidence [ 15 ]. A series of control experiments showed that serial dependence effects could not be accounted for by effects such as priming, hysteresis, explicit memory or expectation.…”
Section: Introductionmentioning
confidence: 99%